2021
DOI: 10.3390/membranes11120933
|View full text |Cite
|
Sign up to set email alerts
|

Putative Internal Control Genes in Bovine Milk Small Extracellular Vesicles Suitable for Normalization in Quantitative Real Time-Polymerase Chain Reaction

Abstract: Bovine milk small extracellular vesicles (sEVs) contain many biologically important molecules, including mRNAs. Quantitative real-time polymerase chain reaction (qRT-PCR) is a widely used method for quantifying mRNA in tissues and cells. However, the use, selection, and stability of suitable putative internal control genes in bovine milk sEVs for normalization in qRT-PCR have not yet been identified. Thus, the aim of the present study was to determine suitable putative internal control genes in milk sEVs for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Nanoparticle size analysis showed that the peak of nanoparticle size distribution was approximately 100 nm in all milk sEVs ( Figure 1 B). These results confirm the presence of milk sEVs in this study [ 28 , 29 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Nanoparticle size analysis showed that the peak of nanoparticle size distribution was approximately 100 nm in all milk sEVs ( Figure 1 B). These results confirm the presence of milk sEVs in this study [ 28 , 29 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 91%
“…Isolation and purification of milk sEVs was carried out as previously described [ 23 , 28 , 29 ], with slight modifications. Briefly, after removing the milk fat by centrifugation at 2000× g for 20 min using an A2506 centrifuge (Kubota, Tokyo, Japan), defatted milk was preheated at 37 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations